JERAMBA-JERAMBA MALAM KARYA MIMI LA ROSE DKK (KUMPULAN CERPEN LOKALITAS LUBUKLINGGAU SEBAGAI BAHAN PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH) - Tri Astuti; Santi Mariami (LP4MK STKIP PGRI Lubuklinggau, 2022)
The study of some short stories in Jeramba-jeramba Malam by Mimi La Rose, et al is the teaching material to find many reinforcement forms for character education ​​of teenagers. The study type was descriptive qualitative with the content analysis method. All data were collected by documentation techniques and library research. There were two stages for analyzing data, such as data reduction and data presentation. Data reduction was used to select and sort data from the literature validly, while data presentation provided conclusions from the results of the discussion. The results of data analysis were concluded that the short story collections of Jeramba-jeramba Malam by Mimi La Rose, et al. are some literary works that describe the locality of Lubuklinggau City and reflect many aspects of character education material formulated by the Ministry of National Education. It supported the demands of the curriculum related to the scope of the selection of teaching materials that are expected today, which should be sourced from local wisdom. Therefore, these short stories can be recommended as the material for reinforcement literacy and character education or as the study material for literary appreciation in schools, especially at secondary schools in Lubuklinggau City.